The Cauchy-Schwarz master class an introduction to the art of mathematical inequalities - Steele, John Michael 1949- (Cambridge University Press, 2010)
Using the Cauchy-Schwarz inequality as the initial guide, this text explains the concepts of mathematical inequalities by presenting a sequence of problems as they might have been discovered, the solutions to which can either be found with one of history's great mathematicians or by the reader themselves